(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The authors analyze the systems of currency regulation and currency control of the member countries of the Eurasian Economic Union. A comparative description of the currency legislation of the EAEU member states is given in terms of the definition of currency regulation bodies, bodies and agents of currency control and their functions. The possibility of creating an institution that promotes the harmonization and unification of monetary systems in order to achieve uniformity of approaches to the implementation of monetary policy within the framework of integration is being considered